2022
DOI: 10.1097/ncc.0000000000001089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Face-to-Face and Phone Call Motivational Interviewing on Cervical Cancer Screening

Abstract: BackgroundHaving regular screening tests largely depends on motivational factors. Motivational interviewing (MI) facilitates the movement through the stages of the transtheoretical model of change.ObjectiveThe aim of this study was to compare the effect of face-to-face and phone call MI on cervical cancer screening.MethodsThis experimental study was conducted on 150 eligible women referred to health centers in Tabriz, Iran. The women were assigned into 3 groups (face-to-face MI, phone MI, or control) using blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The decision support framework conceptualizes the support needed by patients, their families, and their physicians for "difficult" decisions with multiple options. 24 This type of decision-making is on the agenda in 2 key areas including medical ethics and health service research. 25,26 It guides clinicians and researchers to assess participants' decision-making needs, provide decision support interventions (clinical counseling and patient decision tools), and evaluate their effects on decision-making outcomes.…”
Section: Study Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…The decision support framework conceptualizes the support needed by patients, their families, and their physicians for "difficult" decisions with multiple options. 24 This type of decision-making is on the agenda in 2 key areas including medical ethics and health service research. 25,26 It guides clinicians and researchers to assess participants' decision-making needs, provide decision support interventions (clinical counseling and patient decision tools), and evaluate their effects on decision-making outcomes.…”
Section: Study Frameworkmentioning
confidence: 99%
“…The decision support framework conceptualizes the support needed by patients, their families, and their physicians for “difficult” decisions with multiple options 24 . This type of decision-making is on the agenda in 2 key areas including medical ethics and health service research 25,26 .…”
Section: Study Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen mothers could not leave their homes to attend the face-to-face session after randomization and received MI over the phone at baseline. A previous study reported no significant differences between face-to-face and phone call MI [ 27 ]. The MI session started by establishing rapport and showing concern to get the mother to discuss her understanding of oral diseases, their impact on the child’s life and the child’s oral health status and oral healthcare.…”
Section: Methodsmentioning
confidence: 99%